Sun Protection Behaviors of State Park Workers in the Southeastern USA. Issue 5 (27th March 2019) - Nahar, Vinayak K; Wilkerson, Amanda H; Martin, Brian; Boyas, Javier F; Ford, Mary A; Bentley, John P; Johnson, Paul; Beason, Kim R; Black, William H; Brodell, Robert T
Abstract: Background: Due to the nature of their work, state park workers receive substantial exposure to sunlight, putting them at an increased risk of developing skin cancer. Increased use of sun protection behaviors can reduce this risk. Objectives: Using the health belief model (HBM) as a theoretical framework, the purpose of this study was to assess factors associated with sun protection behaviors among state-park workers. Methods: In this cross-sectional study, a convenience sample of participants were recruited from 23 state parks in the Southeastern USA to complete a self-administered questionnaire based on the constructs of the HBM. Results: The sample comprised 310 state park workers. The majority of participants were non-Hispanic White (61.6%), male (63.5%), and were aged 39.56 (±13.97) years on average. The average duration of sun exposure during the workday was reported as 3.51 h (±1.88). Nearly 12% of the participants reported that their workplace had a sun-safety policy and 10% reported receiving sun-safety training at their workplace. The majority of participants reported that they did not sufficiently use sun protection methods. Factors associated with sun protection behaviors included the HBM constructs of perceived benefits outweighing perceived barriers (standardized coefficient = 0.210, P = 0.001), self-efficacy (standardized coefficient = 0.333, P < 0.001), and cues to action (standardized coefficient = 0.179, P = 0.004). Conclusion: Future research should explore the barriers to adopting and enforcing sun-safety policies in the workplace. HBM appears to be efficacious in explaining sun protection behaviors among state park workers. HBM constructs should be considered in future interventions aimed at increasing sun protection behaviors in this population.